Carbon necklace incorporated electroactive reservoir constructing flexible papers for advanced lithium-ion batteries - Du, Min (2020)
Metal–organic frameworks (MOFs) and their derivatives with well‐defined structures and compositions show great potential for wide applications such as sensors, catalysis, energy storage, and conversion, etc. However, poor electric conductivity and large volume expansion are main obstacles for their utilization in energy storage, e.g., lithium–ion batteries and supercapacitors. Herein, a facile strategy is proposed for embedding the MOFs, e.g., ZIF‐67 and MIL‐88 into polyacrylonitrile fibers, which is further used as a template to build a 3D interconnected conductive carbon necklace paper. Owing to the unique structure features of good electric conductivity, interconnected frameworks, electroactive reservoir, and dual dopants, the obtained flexible electrodes with no additives exhibit high specific capacities, good rate capability, and prolonged cycling stability. The hollow dodecahedral ZIF‐67 derived carbon necklace paper delivers a high specific capacity of 1200 mAh g−1 and superior stability of more than 400 cycles without capacity decay. Moreover, the spindle‐like MIL‐88 derived carbon necklace paper shows a high reversible capacity of 980 mAh g−1. Their unique 3D interconnected structure and outstanding electrochemical performance pave the way for extending the MOF‐based interweaving materials toward potential applications in portable and wearable electronic devices.